ACTIVE LEARNING BASED ON BETTER TEACHING AND LEARNING (BTL) TO IMPROVE PROCESS SKILL AND STUDENTS STUDY RESULT - Sukaesih, S.; Pukan, K.K. (Jurnal Pendidikan IPA Indonesia, 2015)
This research was conducted to describe the application of active learning based on Better Teaching and Learning (BTL) in improving process skill and students study result of grade VIII SMP N 21 Semarang.  The methode is classroom Action Research. The  research result reviewed that the increasethe process skill of students at cycle 1 and 2 are :80.95 and 94.29. While the studentsstudy result  above passing grade at the cycles 1and 2 are: 74.0 and 77.0. This result research that applying active learning Based on Better Teaching and Learning could increase the process skill and study result of the students.